2000
DOI: 10.1103/physrevlett.84.5983
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond Time-Resolved Photoelectron Angular Distributions Probed during Photodissociation ofNO2

Abstract: Femtosecond time-resolved photoelectron angular distributions (PADs) are measured for the first time in the molecular frame of a dissociating molecule. Various stages of the dissociation process, NO2-->NO(C Pi)+O(P), are probed using ionization of the NO(C Pi) fragment to NO+(X Sigma(+)). The PADs evolve from forward-backward asymmetric with respect to the dissociation axis at short time delays ( < or =500 fs) to symmetric at long time delays (> or = 1 ps). Changes in the PADs directly reflect the time-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
106
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(111 citation statements)
references
References 24 publications
5
106
0
Order By: Relevance
“…This is possible if ionization leads to fragmentation of the molecule and the electrons can be measured in coincidence with fragment ions recoiling in directions that directly reflect the molecular orientation at the moment of ionization, a condition often referred to as the axial recoil limit. Such coincidence methods have been applied successfully, predominantly to small molecules where synchrotron radiation removes an inner shell electron [6][7][8][9] but also to situations where valence electrons are removed by UV radiation [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…This is possible if ionization leads to fragmentation of the molecule and the electrons can be measured in coincidence with fragment ions recoiling in directions that directly reflect the molecular orientation at the moment of ionization, a condition often referred to as the axial recoil limit. Such coincidence methods have been applied successfully, predominantly to small molecules where synchrotron radiation removes an inner shell electron [6][7][8][9] but also to situations where valence electrons are removed by UV radiation [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that (at least) partial alignment of molecular axes improves the sensitivity of the PAD to electronic character; this alignment can be achieved through photoexcitation, through strong-field alignment methods, or through coincidence imaging. [6][7][8][9][10][11] In the atomic case, alignment of orbital angular momentum serves the same purpose as alignment of molecular axes, and a number of laser-based studies have shown that achieving this through photoexcitation prior to photoionization can lead to a PAD with exquisite sensitivity to the angular momentum composition of the intermediate state. [12][13][14] However, although systematic studies have been performed in which different intermediate electronic states are prepared, generally only a single ionic electronic state has been accessible in each case.…”
Section: Introductionmentioning
confidence: 99%
“…So far, photoelectron-photoion coincident (PEPICO) imaging techniques have been mostly applied in ionization studies using one-photon excitation with synchrotron or He(I) radiation [6 -11]. Only recently, first femtosecond time-resolved PEPICO imaging experiments were reported [12,13], and new theoretical frameworks have been developed to study time-resolved photoelectron dynamics [14,15]. In this Letter we use the full potential of time-resolved coincidence imaging to unravel competing ionization and fragmentation processes in multiphoton excited CF 3 I.…”
mentioning
confidence: 99%
“…He(I)] to probe the dissociation of theà A 2 A 1 state of CF 3 I and measure molecular-frame PADs (MF-PADs) associated with the CF 3 and I fragments [6]. Here we apply femtosecond time-resolved multiphoton excitation of CF 3 I to the region just below theà A 2 A 1 state of CF 3 I and follow the production of CF 3 I fragments using the PEPICO imaging apparatus at Sandia National Laboratories [1,12,13].In the experiments, a regeneratively amplified Ti:sapphire laser operating at 0.7 kHz produces linearly polarized laser pulses at 795 nm. The compressor output, with typical pulse duration of about 100 fs, is frequency doubled and tripled.…”
mentioning
confidence: 99%